2015
DOI: 10.4236/ojog.2015.59071
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Defensins Genes and Vulvovaginal Candidiasis: A Study of Cases

Abstract: Objective: To evaluate the alpha-defensin (α-DF) genes polymorphism in women with vulvovaginal candidiasis and recurrence. Methods: This observational study included clinical vaginal secretion samples collected over four years from 88 women, ranging in age from 18 to 65 years, from medical centers of São Paulo and Mogi das Cruzes, Brazil. Thirty-six of these women were asymptomatic (control group) and 52 presented clinical condition compatible with vulvovaginitis (38 primary or episodic as non-recurrent forms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…VVC can evolve in recurrent VVC (RVVC) when four or more episodes of VVC occur during a year, affecting 7-8% of women that experienced a first episode in their childbearing age and resolving after menopause [14]. Boatto and co-workers observed that genetic variations within DEFA1 and DEFA3 genes could be related with RVVC and its severity [61].…”
Section: α-Defensinsmentioning
confidence: 99%
“…VVC can evolve in recurrent VVC (RVVC) when four or more episodes of VVC occur during a year, affecting 7-8% of women that experienced a first episode in their childbearing age and resolving after menopause [14]. Boatto and co-workers observed that genetic variations within DEFA1 and DEFA3 genes could be related with RVVC and its severity [61].…”
Section: α-Defensinsmentioning
confidence: 99%